Pengaruh Peraturan Sekolah Adaptif terhadap Sikap Displin Peserta Didik dalam Human Centered Society 5.0 SMK Darul Falah Bulok Tanggamus - Muhisom Muhisom; Febra Anjar Kusuma; Dian Permata Sari; Rima Yuni Saputri (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the impact of adaptive school regulations on the formation of students’ disciplinary attitudes within the context of a human-centered Society 5.0 at SMK Darul Falah Bulok, Tanggamus. This research is motivated by the school’s need to foster discipline that is not merely based on compliance, but rather develops from students’ self-awareness and internal regulation. The study employs a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation involving the principal, teachers, and students as the main informants. The findings indicate that adaptive school regulations are characterized by flexibility, contextual relevance, participatory implementation, and the wise integration of technology. The implementation of these regulations has a positive impact on various aspects of student discipline, including improved punctuality, responsible use of technology, orderly classroom behavior, enhanced learning motivation, and consistent guidance through collaboration among schools, teachers, students, and parents. Optimization strategies include strengthening digital literacy, applying personalized approaches and individual counseling, conducting periodic monitoring, and encouraging active parental involvement. The main conclusion of this study is that adaptive school regulations are effective in shaping students’ disciplinary attitudes that are relevant to the demands of the Society 5.0 era and contribute to the development of humane, flexible, and student-centered educational policies. This study aims to analyze the impact of adaptive school regulations on the formation of students’ disciplinary attitudes within the context of a human-centered Society 5.0 at SMK Darul Falah Bulok, Tanggamus. This research is motivated by the school’s need to foster discipline that is not merely based on compliance, but rather develops from students’ self-awareness and internal regulation. The study employs a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation involving the principal, teachers, and students as the main informants. The findings indicate that adaptive school regulations are characterized by flexibility, contextual relevance, participatory implementation, and the wise integration of technology. The implementation of these regulations has a positive impact on various aspects of student discipline, including improved punctuality, responsible use of technology, orderly classroom behavior, enhanced learning motivation, and consistent guidance through collaboration among schools, teachers, students, and parents. Optimization strategies include strengthening digital literacy, applying personalized approaches and individual counseling, conducting periodic monitoring, and encouraging active parental involvement. The main conclusion of this study is that adaptive school regulations are effective in shaping students’ disciplinary attitudes that are relevant to the demands of the Society 5.0 era and contribute to the development of humane, flexible, and student-centered educational policies.